Enhancing productivity of perennial aromatic grasses on marginal lands through plant growth promoting rhizobacteria. (11th August 2022) - Maddhesiya, Pawan Kumar; Singh, Kripal; Kumar, Devendra; Singh, Rana Pratap
Abstract: The cultivation of perennial aromatic grasses on marginal lands is a socio‐economically and ecologically sustainable approach. However, the studies on assessment of the potential efficacies of consortium of plant growth promoting rhizobacteria (PGPR) in enhancing the productivity of perennial aromatic grasses on marginal lands are rare. In this study, therefore, we studied the effect of PGPR consortium ( Pseudomonas protegens and two strains of Bacillus paramycoides ) on yield and economics of four perennial aromatic grasses ( Vetiveria zizanioides, Cymbopogon citratus, C. martinii, and C. winterianus ) in slightly alkaline (pH >8.50) soil. A field experiment was established in a complete randomized block design with two treatments (i.e. with PGPR consortium and without PGPR consortium) and three replications. The changes in growth (height, number of slips, and leaf area index), productivity (fresh shoot‐root biomass and oil yield), quality (important secondary metabolites), and economics (cost of cultivation, gross, and net return) in response to PGPR were observed at three harvests. The species‐specific effects of PGPR were found on the growth and productivity of perennial aromatic grasses. On an average, the highest increase in growth and productivity with the effect of PGPR was found in V. zizanioides followed by other grasses. The highest oil yield 16.38, 71.14, 53.13, and 49.49 kg ha −1 were recorded at third harvest in PGPR consortium treated plots for V. zizanioides, C. citratus, C. martinii, and C. winterianus, respectively. The agronomical economics show the highest net return of 2094.95 $US in the cultivation of V. zizanioides with the application of PGPR.